124k views
0 votes
Simplify the expression below.

4x+ 3(2x−1) − 4x

2 Answers

2 votes

Answer:

6x - 3

Explanation:

4x + 3(2x - 1) - 4x

Distribute, multiply every term inside the parenthesis by the term outside of it,

4x + (3)(2x) + (3)(-1) - 4x

Simplify,

4x + 6x - 3 - 4x

Simplify further, combine like terms,

6x - 3

User Sam Yi
by
6.3k points
3 votes

Answer:

=6x−3

Explanation:

Let's simplify step-by-step

4x+3(2x−1)−4x

Distribute:

=4x+(3)(2x)+(3)(−1)+−4x

=4x+6x+−3+−4x

Combine Like Terms:

=4x+6x+−3+−4x

=(4x+6x+−4x)+(−3)

=6x+−3

User Spilot
by
5.4k points